A Brief Screen to Detect Cannabis Use Disorder Among Incarcerated Youth. Issue 3 (3rd May 2020) - Delaney, Daniel; Balestrieri, S. G.; Bassett, Shayna S.; Stein, L. A. R.
Abstract: Chronic cannabis use among adolescents is associated with many adverse health effects. One group of adolescents at the highest risk for chronic use are those involved in the juvenile justice system. While cannabis use disorder (CUD) screening tools have recently become briefer, ideally a single-item measure could be used to efficiently identify those who likely meet the criteria for CUD. These analyses aimed to determine whether a cut score, based on the frequency of cannabis use in the past year, could predict whether participants met the criteria for CUD among a sample of juvenile detainees ( n = 189). DSM-IV diagnostic criteria for CUD were mapped onto current DSM-V criteria to determine a diagnosis. Two CUD severity cut scores were explored: (1) a cut score that distinguished those with no CUD or mild CUD from those who have a moderate or severe CUD, and (2) a cut score that distinguishes those with no, mild, or moderate CUD from those who have severe CUD. t -Tests revealed significant differences in the number of cannabis use days in the past year by both sets of CUD comparison categories. When predicting none/mild vs. moderate/severe CUD, the optimal cut score was found to be ≥24 cannabis use days; for no/mild/moderate vs. severe CUD, the optimal cut score was ≥57 days. Hierarchical regression demonstrated the addition of cannabis use days provided significant incremental validity beyond the proportion of friends who use substances when predicting diagnostic symptom count. This 1-item cannabis screener is an effective tool to quickly determine the need for further assessment of CUD.